Matching physicians to newly arrived refugees in a context of physician shortage: innovation through advocacy. Issue 1 (12th March 2014) - Brunger, Fern; S. Duke, Pauline; Kenny, Robyn
Abstract : Purpose: – Access to a continuum of care from a family physician is an essential component of health and wellbeing. Refugees have particular barriers to accessing medical care. The MUN MED Gateway Project is a medical student initiative in partnership with a refugee settlement agency that provides access to and continuity of health care for new refugees, while offering medical students exposure to cross-cultural health care. This paper aims to report on the first six years of the project. Design/methodology/approach: – Here the paper reports on: client patient uptake and demographics, health concerns identified through the project, and physician uptake and rates of patient-physician matches. Findings: – Results demonstrate that the project integrates refugees into the health care system and facilitates access to medical care. Moreover, it provides learning opportunities for students to practice cross-cultural health care, with high engagement of medical students and high satisfaction by family physicians involved. Originality/value: – Research has shown that student run medical clinics may provide less than optimum care to marginalized patients. Transient staff, lack of continuity of care, and limited budgets are some challenges. The MUN MED Gateway Project is markedly different. It connects patients with the mainstream medical system. In a context of family physician shortage, this student-run clinic project provides access to medical care for newly arrived refugees in a way that is effective, efficient, and sustainable.